If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 + 6 = 4 + 7x + -4x Reorder the terms: -2 + 6 + 3x = 4 + 7x + -4x Combine like terms: -2 + 6 = 4 4 + 3x = 4 + 7x + -4x Combine like terms: 7x + -4x = 3x 4 + 3x = 4 + 3x Add '-4' to each side of the equation. 4 + -4 + 3x = 4 + -4 + 3x Combine like terms: 4 + -4 = 0 0 + 3x = 4 + -4 + 3x 3x = 4 + -4 + 3x Combine like terms: 4 + -4 = 0 3x = 0 + 3x 3x = 3x Add '-3x' to each side of the equation. 3x + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 7-4n=13 | | -32-3/5f=-17 | | 4x-1=2(2x+3) | | h=-38x+77813 | | 96-5g=51 | | 7x+8=6x+1 | | 7h-27=36 | | 0.10x+0.25(11-x)=1.70 | | 25x+10(11-x)=1.70 | | x+(11-x)=1.70 | | 26=14-2m | | 5=9-2x | | 6y+9-4y=-3 | | 4(w+0.3)=66.48 | | -2(t-9)-(t+2)=1 | | 42=3x+12 | | 0=8z+8 | | 9m=11 | | -4b-5+2b=10 | | 3(6z-1)-5(z+7)=9(z+1) | | 2x-8+3x=7 | | -2m+5=-2m-5 | | 7.5x+2=-28 | | -2m+5=-2m+5 | | -4=2t-2 | | -2m+5=2m+5 | | 15=7-2p | | -8+4s=-16 | | 7(1x+8)=-14 | | 5(-6x-2)=110 | | -3z-8=-26 | | 55+15h=92.50 |